Frost tolerance improvement in pea and white lupin by a high-throughput phenotyping platform - Franguelli, Nicolò; Cavalli, Daniele; Notario, Tommaso; Pecetti, Luciano; Annicchiarico, Paolo (Frontiers in Plant Science, 2024)
The changing climate could expand northwards in Europe the autumn sowing of cool-season grain legumes to take advantage of milder winters and to escape the increasing risk of terminal drought. Greater frost tolerance is a key breeding target because sudden frosts following mild-temperature periods may produce high winter mortality of insufficiently acclimated plants. The increasing year-to-year climate variation hinders the field-based selection for frost tolerance. This study focused on pea and white lupin with the objectives of (i) optimizing an easy-to-build, high-throughput phenotyping platform for frost tolerance assessment with respect to optimal freezing temperatures, and (ii) verifying the consistency of genotype plant mortality responses across platform and field conditions. The platform was a 13.6 m2 freezing chamber with programmable temperature in the range of −15°C to 25°C. The study included 11 genotypes per species with substantial variation for field-based winter plant survival. Plant seedlings were evaluated under four freezing temperature treatments, i.e., −7°C, −9°C, −11°C, and −13°C, after a 15-day acclimation period at 4°C. Genotype plant mortality and lethal temperature corresponding to 50% mortality (LT50) were assessed at the end of a regrowth period, whereas biomass injury was observed through a 10-level visual score based on the amount of necrosis and mortality after recovery and regrowth. On average, pea displayed higher frost tolerance than white lupin (mean LT50 of −12.8 versus −11.0°C). The genotype LT50 values ranged from −11.6°C to −14.5°C for pea and from −10.0°C to −12.0°C for lupin. The freezing temperature that maximized the genotype mortality variation was −13°C for pea and −11°C for lupin. The genotype mortality at these temperatures exhibited high correlations with LT50 values (0.91 for pea and 0.94 for lupin) and the biomass injury score (0.98 for pea and 0.97 for lupin). The frost tolerance responses in the platform showed a good consistency with the field-based winter survival of the genotypes. Our study indicates the reliability of genotype frost tolerance assessment under artificial conditions for two cool-season grain legumes, offering a platform that could be valuable for crop improvement as well as for genomics and ecophysiological research.